A risk- and complexity-rating framework for investment products - KOH, Benedict S. K. (Institutional Knowledge at Singapore Management University, 2015)
Many investors who bought such investments as Lehman Brothers’ minibonds did not understand the products’ complicated features. This fact suggests that if the inherent risk and complexity of products’ structure are not clearly understood by investors, they will be unable to make informed decisions. Some practitioners have recently attempted to calibrate product complexity. The authors propose a framework for classifying investment product risk and complexity separately with a list of factors that contribute to these attributes. They demonstrate the framework’s simplicity and usefulness in helping investors make informed decisions, showing that it can be used to calibrate a variety of investment products